IMPLEMENTATION OF DIGITAL INFORMATION SYSTEMS TO IMPROVE OPERATIONAL EFFICIENCY IN RETAIL SMEs - Rara azahra; Zahra Ardiana Putri; Ryndian Gusty; Muhammad Dalim (Asian Journal of Islamic Economic Studies, 2026)
This research aims to analyze the implementation of digital information systems in increasing operational efficiency in micro, small, and medium enterprises (UMKM) in the retail sector, by taking a case study at Indomaret Medan. Digital transformation becomes a vital need for MSMEs in the era of industry 4.0 to increase competitiveness and operational efficiency. The research method used is qualitative descriptive with data collection techniques through in-depth interviews and direct observation of the store's operational process. The research results show that the implementation of the digital information system at Indomaret covers various operational aspects, including digital cash register system, technology-based attendance system, human resource management system, and technical support through Electronic Data Processing (EDP). Research findings indicate that digitalization has a positive impact on operational efficiency, especially in transaction speed, data accuracy, and employee performance monitoring. However, there are technical obstacles faced, especially related to the stability of the internet connection that affects the smoothness of the system. This research provides a theoretical contribution in understanding the factors that determine the success of information system implementation in retail MSMEs and provides practical recommendations for business actors who want to do digital transformation.